Pengaruh Kunjungan dan Pengeluaran Wisatawan Mancanegara Terhadap Akomodasi Hotel Bintang di Indonesia - Khairatul Nisa; Puti Andiny; Yani Rizal; Safuridar Safuridar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study analyzes the impact of international tourist arrivals and their spending on the occupancy rate of star-rated hotels in Indonesia from 2009 to 2023. Using a quantitative approach with multiple linear regression, the study examines the relationship between two independent variables nternational tourist arrivals and average tourist spending and the dependent variable, which is the occupancy rate of star-rated hotels. Data for this research were sourced from the Central Statistics Agency (BPS), the Ministry of Tourism, and Bank Indonesia. The analysis results show that the number of international tourist arrivals does not significantly affect the occupancy rate of star-rated hotels. However, average tourist spending has a significant negative effect, indicating that tourists with higher spending tend to choose higher-star hotels. The simultaneous F test reveals that both variables jointly have a significant effect on hotel occupancy rates. The coefficient of determination (R²) of 45.52% indicates that both independent variables can explain the variation in the occupancy rate of star-rated hotels. Based on these findings, it is recommended that the government and tourism industry stakeholders focus on promoting destinations that attract high-spending tourists and improving the quality of star-rated hotel accommodations to meet the preferences of international tourists.